Efeito do óleo de peixe sobre a via das quinureninas em um modelo de depressão induzido pelo hormônio adrenocorticotrófico em camundongos - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Depression is an increasingly present disorder in the population, in which the pathophysiology and treatment have been studied by various animal models. Studies show that depression and inflammatory pathways are related, which is the induction of indoleamine 2,3-dioxygenase (IDO) enzyme by inflammatory cytokines, wherein activation of this enzyme results in the breakdown of tryptophan by means of quinureninas, which results in the formation of several neuroactive metabolites. Stress seems to be one of the main environmental factors that predispose an individual to depression, which has a profound impact on the development of psychopathology that affect various physiological processes such as endocrine, immune and central nervous system. In response to stress, the hypothalamus secretes corticotropin releasing hormone (CRH), which stimulates the adeno-pituitary to release adrenocorticotrophic hormone (ACTH) into the bloodstream. Recent research has shown that nutritional deficiency of omega-3 family of polyunsaturated fatty acids is directly related to the prevalence and severity of depression. Supplementation with fatty acids during critical periods of the development of the central nervous system (CNS), are essential for cortical maturation. Thus the present study aimed to evaluate the effect of fish oil on the path of quinureninas in a model of depression induced by the hormone ACTH. Administration of fish oil could reverse several parameters such as the activity of IDO, KMO, GSH, and the products formed on the path of quinureninas (KP) showing that fish oil is effective in reducing damage caused by adrenocorticotropic hormone (ACTH) in mice.
Keywords: Via da quinurenina; ACTH; Depressão; Estresse oxidativo; Via the kynurenine; Depression; Oxidative stress; CNPQ::CIENCIAS AGRARIAS